From Quality to Profitability: The Link between Service, Product Quality, and Customer Satisfaction at PT Mandiri Utama Finance - Dewi, Komang Trisna Sari; Saputra, Kadek Juni (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study investigates the influence of service quality and product quality on customer satisfaction at PT Mandiri Utama Finance, Buleleng Regency, and explores the broader implication of customer satisfaction as a driver of business profitability. Employing a quantitative approach, data were collected through questionnaires distributed to customers and analyzed using SPSS version 21.0. The analysis involved validity and reliability tests, classical assumption testing, multiple linear regression, goodness-of-fit evaluation, and hypothesis testing. The findings reveal that both service quality and product quality have a positive and significant effect on customer satisfaction. Furthermore, the study highlights that enhancing these quality dimensions is not only essential for improving satisfaction but also contributes to the company’s long-term financial performance by fostering stronger customer relationships and retention.